Zarys kształcenia politycznego w Niemczech w latach 1950–1990 - Depczyńska, Paulina (Biuletyn Historii Wychowania, 2016)
The article presents the concept of political education in Germany in the years 1950-1990, specifically taking into consideration its role in building democracy, as well as identity and the development of civic competences. This paper also outlines the terminological problems in civic education from the Polish and German language perspective, and the institutional and legal determinants used in political education. The main point of reflection is the analysis of the stages in the institutional development of civic education in Germany in the years 1950-1990. The final conclusions may be useful in social and political studies, or in the implementation of innovative systemic solutions in civic education today.